Peranan Modal Sosial Rapatan ke atas Pendayaupayaan Ekonomi Orang Kuala (Sains Humanika, 2012)
Relationship between Orang Asli and the outside community are often seen from the negative view in which they are in a disadvantage situation. This is because the relationship is in the form of oppressingand exploting the Orang Asli. But rarely the relationship which known as bridging social capital is seen as an opportunity for Orang Asli to increase their income and to achieve economic empowerment. To examine the realities, this paper raises several questions, the reality of bridging social capital; existence of economic empowerment and role of bridging social capital to economic empowerment among Orang Kuala. This study was carried out using a qualitative approach which implement the in-depth interview method on Orang Kuala who are involved in second-hand goods business in the Bumiputera Dalam village, Rengit Johor. The study showed that the Orang Asli owned a particular bridging social capital andthey had achieved economic empowerment. This study found that bridging social capital has a role in economic empowerment. Reality shows that the effort to bring Orang Asli into mainstream systems has shown a positive impact.
Keywords: Orang Kuala bridging social capital; economic empowerment through business involvement; the role of bridging social capital on economic empowerment